2013
DOI: 10.4103/0973-029x.110725
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc oncogene expression in selected odontogenic cysts and tumors: An immunohistochemical study

Abstract: Aim:To investigate the role of c-Myc oncogene in selected odontogenic cysts and tumors.Materials and Methods:Ten cases each of ameloblastoma, adenomatoid odontogenic tumor (AOT), odontogenic keratocyst (OKC), dentigerous cyst, and radicular cyst were selected and primary monoclonal mouse anti-human c-Myc antibody was used in a dilution of 1: 50. Statistical Analysis was performed using Mann Whitney U test.Results:80% positivity was observed in ameloblastoma, AOT and OKC; 50% positivity in radicular cyst and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Data are shown as the mean ± SD from three independent experiments. *P < 0.05 Jun 22 and c-Myc, 23 were detected in ameloblastoma tissues. Their expression was upregulated under elevated HP at both mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Data are shown as the mean ± SD from three independent experiments. *P < 0.05 Jun 22 and c-Myc, 23 were detected in ameloblastoma tissues. Their expression was upregulated under elevated HP at both mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 86%
“…In hTERT + ‐AM cells, HP‐induced activation of β‐catenin signalling was blocked by DKK1, suggesting that this process depends on the Wnt co‐receptors LRP5/6. Wnt/β‐catenin signalling downstream targets, including LEF‐1, cyclin D1, c‐Jun and c‐Myc, were detected in ameloblastoma tissues. Their expression was upregulated under elevated HP at both mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…While ameloblastoma is locally aggressive and can perforate the cortical bone plate and infiltrate soft tissues, AOT is encapsulated with limited growth potential and very low tendency of recurrence. Notably, both the odontogenic tumours show expression of the MAPK transcriptional targets, cyclin-D1 and c-Myc, which regulate cell proliferation [21][22][23][24][25]. In colorectal cancer, it has been shown that BRAFV600E and KRASG12V oncogenes have a different impact on morphology and invasive phenotype [26].…”
Section: The Mapk Pathway Ameloblastoma and Adenomatoid Odontogenic mentioning
confidence: 99%
“…The C-myc proto-oncogene, which was first detected in Burkitt's lymphoma, is over-expressed in most tumors [ 6 , 7 ], including oral squamous cell carcinoma (OSCC) [ 8 ]. As an oncogenic transcription factor, the C-myc protein recognizes the E-box recognition site and several related, non-canonical sequences in the promoter regions of target genes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%